Implementasi Tari Kreasi Luwu Untuk Meningkatkan Motorik Kasar Anak - Mutiara; Dwiwansyah, Lisa Aditya; Eka Poppi Hutami; Pertiwi Kamariah Hasis; Rifa’ah Mahmudah Bulu (Jurnal Pendidikan Anak Usia Dini Indonesia, 2024)
The type of research used is Classroom Action Research (PTK), with two cycles, namely Cycle I which consists of 4 meetings and Cycle II which consists of 4 meetings. The subjects of this research were 15 children from group B of the Pembina Baebunta Kindergarten for the 2022-2023 academic year, consisting of 6 boys and 9 girls. The data collection techniques for this research are observation and documentation. The research instrument used was an assessment rubric for student observation sheet guidelines. The data collected was then analyzed using data collection techniques through observation, documentation, reflection, evaluation and quantitative data analysis techniques. The success of this research is determined by the research results scores which show an increase in children's learning outcomes. The score in the initial or pre-action condition was 31.25% of all indicators and did not meet the good category in Cycle I with an average observation score of 58% of all indicators and did not meet the good category. Cycle II with an overall average score of 89.5% of all indicators and reached the good category. Thus, this classroom action research (PTK) was successful so that the researchers recommended learning using Luwu Creation Dance to improve children's gross motor development at Pembina Baebunta Kindergarten.